Structure and dielectric breakdown strength of nano calcium carbonate/polypropylene composites. Issue 1 (8th July 2013) - Virtanen, Suvi; Ranta, Hannes; Ahonen, Susanna; Karttunen, Mikko; Pelto, Jani; Kannus, Kari; Pettersson, Mika
ABSTRACT Nanodielectrics, a 21st‐century phenomena, is envisioned to be the answer for material challenges in progressive high‐voltage technology. It is well known that the proper dispersion of nanoparticles plays a key role in improving the dielectric properties of a material, but to understand where changes in the properties of a material originate, it is also essential to reveal the multiscale structure of the material. In this study, the dielectric permittivity, breakdown strength, and structure of nano calcium carbonate (nano‐CaCO3)/polypropylene composites with 1.8–8.1 wt % doping were characterized systematically. The combined results from transmission electron microscopy, Raman microscopy, and optical microscopy show that the quality of nanodispersion was similar in all of the filler concentrations studied. However, all of the samples also contained smoothly distributed microparticles. The density of the microparticles increased exponentially when the concentration of nano‐CaCO3 was increased in the manufacturing process. The dielectric direct‐current breakdown of the composites had a maximum at 1.8 wt % concentration and then decreased as the filler concentration was increased. The differences could be explained by the existence of large microparticles rather than the quality of the nanoparticle dispersion; this indicated the importance of multiscale characterization. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39504.